Sinergitas Masyarakat Lokal Dalam Pengembangan Agrowisata Pada Desa Wisata: Studi Kasus Desa Kalikesek - Aqila, Elmash Nafa; Nisa, Savina Khoirun ’; Firmansyah, Bobby; Yuliana, Moudyva Nazara; Dhyaulhaq, Muhammad Ammar (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Kalikesek Tourism Village is one of the tourism villages in Limbangan District, Kendal Regency. The potential of agriculture and plantations in Kalikesek Village is very promising to support agrotourism. This study was conducted to determine the synergy of local communities towards the development of agrotourism areas, to determine the potential for agrotourism development, to determine the challenges of agrotourism development, and to formulate agrotourism development strategies. The study used qualitative research methods. The results of the study showed that the Kalikesek community worked together in developing agrotourism areas. The challenges faced were regarding waste problems, pros and cons and investment problems. The strategy that will be implemented is progressive by developing all potentials and opportunities optimally.